2016
DOI: 10.1016/j.ejpn.2015.10.001
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of illness perceptions to fatigue and sleep problems in youngsters with epilepsy

Abstract: Fatigue Sleep problems Epilepsy a b s t r a c tPurpose: The present study aims to explore the extent to which gender, epilepsy severity and illness perceptions predict fatigue and sleep problems in youngsters with epilepsy.Method: Structured interviews were conducted in 100 young patients (Mage ¼ 13,9, SD ¼ 2.21; 41% girls) and data were analyzed by means of multiple hierarchical regression analyses.Results: Most patients (91%) were well controlled by anti-epileptics; 3% had infrequent seizures and 6% were pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Conceptually, the eight-item B-IPQ captures three aspects of illness perception: cognitive (5 items) and emotional (2 items) dimensions of illness representations and illness coherence (1 item). There is no consensus in the literature whether B-IPQ scores should be interpreted as eight items on three subscales (cognitive and emotional components of illness representations and illness comprehensibility) [16, 17] or as seven items with two subscales (cognitive and emotional components of representations) [18]. …”
Section: Introductionmentioning
confidence: 99%
“…Conceptually, the eight-item B-IPQ captures three aspects of illness perception: cognitive (5 items) and emotional (2 items) dimensions of illness representations and illness coherence (1 item). There is no consensus in the literature whether B-IPQ scores should be interpreted as eight items on three subscales (cognitive and emotional components of illness representations and illness comprehensibility) [16, 17] or as seven items with two subscales (cognitive and emotional components of representations) [18]. …”
Section: Introductionmentioning
confidence: 99%
“…The protocol for the present intervention study was approved by the Ethical Research Committee of Pendeli's Children Hospital and is part of a larger study aiming at the creation of a brief and inexpensive psycho-educational program that could become part of the standard specialized epilepsy care. To this end, we first conducted studies that showed that illness cognitions explained important parts of the variance in psychological distress and quality of life as well as in fatigue and sleep problems in children and adolescents with epilepsy [2,3]. Based on these studies we developed the intervention, which is described below.…”
Section: Participants and Proceduresmentioning
confidence: 99%
“…Initially, 400 medical records of children and adolescents at the Epilepsy Clinic were consecutively examined and reviewed for their eligibility for the study. After examination of the medical records by a neurologist, children and adolescents who fulfilled the listed inclusion criteria were approached during their prescheduled visits and the first 100 who agreed to participate were included in a larger study that is described elsewhere [2,3].…”
Section: Participants and Proceduresmentioning
confidence: 99%
See 2 more Smart Citations